Online Signature Verification: State of the art - El-Henawy, Ibrahim; Rashad, Magdy; Nomir, Omima; Ahmed, Kareem (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
online or Dynamic signature verification (DSV) is one of the most acceptable, intuitive, fast and cost effective tool for user authentication. DSV uses some dynamics like speed, pressure, directions, stroke length and pen-ups/pen-downs to verify the signer’s identity. The state of the art in DSV is presented in this paper. several approaches for DSV are compared and the most influential techniques in this field are highlighted. We concentrate on the relationship between the verification approach used (the nature of the classifier) and the type of features that are used to represent the signature.